Tampering Detection on Digital Evidence for Forensics Purposes (2018)
In terms of digital evidence, images of a crime scene play an important role in a legal process; therefore it is essential to guarantee their chain of custody. If the image is tampered with operations such as cropping, duplicity or blurring of objects, there must be a mechanism that identifies the existence of such manipulation. In this paper, a solution to the chain of custody based on a technique known as watermarking is proposed. In order to validate the sensitivity and effectiveness of the proposed system, six classes of manipulations are applied to watermarked images; finding a high sensitivity to small manipulations (e.g 0.25% of the image size), since in all cases the manipulation was identified. With the proposed solution, legal authority can rely on the chain of custody of the digital evidence.